What Kind of Institutional Configuration Incentivizes Farmers’ Behavior in Ecological Value Co-Creation of Cultivated Land? - Siyu Zhang; Weiyan Hu; Li Chen; Yu Zhang; Liye Wang (Land)
Innovating institutional incentives and promoting multiple-subject interaction and cooperation to create ecological value of cultivated land are practical requirements for the sustainable protection of cultivated land and high-quality development of agriculture and rural areas. We performed a survey questionnaire of 862 farmers in the Wuhan Metropolitan Area and used the fuzzy set qualitative comparative analysis (fsQCA) method to explore the institutional configuration effect of farmers’ behavior in the ecological value co-creation of cultivated land (FBEVCCL). The institutional configuration characteristics of the ecological value co-creation of cultivated land was analyzed, and we propose institutional optimization suggestions for the ecological value co-creation of cultivated land. The research results demonstrated the following: (1) A single institutional element does not constitute a necessary condition for the FBEVCCL, and it is necessary to analyze the institutional configuration effect. (2) Four institutional configurations lead to high-level FBEVCCL. Both formal and informal configurations have important impacts on the FBEVCCL, but the guidance, subsidies, and constraints of formal institutions are often the core driving factors, complemented by the shaping of farmers’ values to jointly enhance the FBEVCCL. The formal institutions of publicity and guidance, rewards and subsidies, and disciplinary constraints can to some extent replace each other. (3) The three institutional configurations lead to low-level FBEVCCL, and the lack of informal and formal institutions for incentives and punishments is the main reason for low-level FBEVCCL. In the future, we should further standardize the reward and punishment mechanism, enhance farmers’ green production skills, and sustainably enhance the behavior of farmers in the ecological value co-creation of cultivated land.